Sovereign Justice Global Justice in a World of Nations - Aurelio, Diogo (De Gruyter, 2010)
Over the past years global justice has established itself as one of the new and most promising frontiers of political theory. Sovereign Justice collects valuable contributions from scholars of both continental and analytic tradition, and aims to investigate into the relationship between global justice and the nation state. It deals with the moral relevance of national boundaries and cosmopolitanism, and takes into account the most influential traditions that shape current approaches to the subject, especially those descending from Rawls and Kant.